2011
DOI: 10.1002/aoc.1836
|View full text |Cite
|
Sign up to set email alerts
|

From poly(dialkylstannane)s to poly(diarylstannane)s: comparison of synthesis methods and resulting polymers

Abstract: The efficiency and applicability of three different methods to synthesize polystannanes with different side chains are described. By means of dehydrogenative coupling utilizing the transition metal catalyst RhCl(PPh 3 ) 3 (Wilkinson's catalyst), n-Bu 2 SnH 2 reached the highest molar masses. Dehydrogenetive coupling in the presence of tetramethylethylenediamine could be best employed for (4-n-BuPh) 2 SnH 2 . Wurtz coupling using sodium in liquid ammonia was best suited for Ph 2 SnCl 2 . Next to the above-menti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…It was previously shown that poly(dialkylstannane)s exhibit an absorption maximum in the region of 370e410 nm [4aec, 19,23,24], which is caused by delocalization of the s-electrons of the tin atoms along the polymer backbone. In several reports, the degree of degradation of these materials was evaluated from the UVeVis spectroscopy [4a,23,24].…”
Section: Polymer Characterization Of 18 and 19mentioning
confidence: 99%
“…It was previously shown that poly(dialkylstannane)s exhibit an absorption maximum in the region of 370e410 nm [4aec, 19,23,24], which is caused by delocalization of the s-electrons of the tin atoms along the polymer backbone. In several reports, the degree of degradation of these materials was evaluated from the UVeVis spectroscopy [4a,23,24].…”
Section: Polymer Characterization Of 18 and 19mentioning
confidence: 99%
“… 4 16 Many years later the concept was revisited and also transition metal catalysts have been applied to perform selective dehydrocoupling reactions with tin dihydrides to obtain tetraorganodistannanes or organotin polymers ( Scheme 1 ). 17 23 In the case of the formation of tetraorganodistannanes the formation via intermediate generation of the stannylene was proposed. 17 …”
Section: Introductionmentioning
confidence: 99%
“…These reaction conditions afforded the polymerization of (n-Bu)2SnCl2 and (n-Oct)2SnCl2 to the polystannanes (n-Bu2Sn)n and (n-Oct2Sn)n having molar masses 8.0 × 10 3 and 6.0 × 10 3 Da respectively. The material produced from the reaction of Ph2SnCl2 under similar conditions was insoluble in organic solvents at room or elevated temperatures making molecular weight determination impossible; however the elemental composition of the isolated yellow product was in agreement with that of (Ph2Sn)n. 130 In general, there are several disadvantages of the Wurtz synthetic method; it has limited tolerance to functional groups, the yields are moderate, the reproducibility is poor and it is dangerous due to the pyrophoric nature of Na metal and harsh reaction conditions. 131…”
Section: Wurtz Couplingmentioning
confidence: 99%
“…This may be a result of steric crowding at tin as a result of the C,O-chelating ligands. Lechner et al 130 used TMEDA for the polymerization of R2SnH2 (R = nbutyl, phenyl, 4-n-butylphenyl) to polymers 251 and 252 which gave 119 Sn NMR resonance at -197 ppm, a typical region for polystannanes. Figure 57: 119 Sn NMR (C6D6) spectrum of 251.…”
Section: Non-metal Catalyzed Dehydrocouplingmentioning
confidence: 99%
See 1 more Smart Citation